The Influence of Instructional Leadership on the Performance of Students in South African Schools - Ncokazi Ayanda; Agyeman Nana Yaw (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The quality of educational outcomes has emerged as a critical factor in determining the progress and success of both societies and individuals. Studies suggest that effective instructional leadership impacts learner outcomes in schools. The objective of the study is to explore the influence of instructional leadership on the performance of students in South Africa. The study employed the qualitative approach with a case study design to investigate the impact of instructional leadership on the performance of students. Purposive sampling was used to select six participants. Semi-structured interviews were adopted to gather data, and thematic analysis was utilised to identify themes and patterns that emerged from the study. The findings of the study showed that an improved school environment and positive school cultures contribute to enhanced performance of students. In addition, the study discovered that addressing the individual learning differences of students and removing barriers to learning is key to enhancing students learning. Consequently, there is a need for instructional leaders to emphasise teaching and learning, as well as establish a clear school vision to improve the learning culture and school environment. The study concluded that instructional leadership play a significant role in fostering the quality of teaching and learning practices in schools. The findings of this study imply that schools should emphasise and empower leaders with instructional leadership skills to achieve improved educational outcomes in schools.